Cardiac Structure and Function of Elite Australian Jockeys Compared to the General Population: An Observational Cross-Sectional Study - Angela Farley; Hunter Bennett; Roger Eston; Rebecca Perry (SpringerOpen, 2024)
Abstract Background Research highlights the intense physiological demands of thoroughbred racing on jockeys, with elevated heart rates and substantial oxygen uptake, confirming the rigorous physical nature of the sport, however, the cardiovascular changes resulting from the physical demands of thoroughbred racing remain unexplored in Australian jockeys. Therefore, the objective of this study was to compare measures of cardiac structure and function of professional Australian jockeys to that of the general population and to determine if there are differences in heart structure and function detected using echocardiography. Methods Forty-six jockeys and thirty-three participants from the general population underwent two-dimensional echocardiography, which included all standard views and measurements. Each measurement was compared between groups using a Mann-Whitney U test. Results Groups were matched for age (jockeys (35 ± 12 years) and controls (36 ± 13 years)). Jockeys were shorter (1.64 ± 0.07 m vs. 1.75 ± 0.09 m, p < 0.001), lighter (56.5 ± 6.0 kg vs. 74.2 ± 12.9 kg, p < 0.001) and had a lower body surface area (BSA) (1.55 ± 0.17 m2 vs.1.9 ± 0.2 m2, p < 0.001). Jockeys had a larger absolute left ventricular (LV) end diastolic volume than the control group (120 ± 18.2 ml vs. 109.3 ± 29.0 ml, p = 0.05) which had a larger variation when indexed for BSA (78.0 ± 12.2 ml/m2 vs. 57.5 ± 13.3 ml/m2, p < 0.001). Jockeys demonstrated a higher LV mass index (79.4 ± 18.1 g/m2 vs. 64.2 ± 15.4 g/m2, p < 0.001). Left atrial volume index was larger in jockeys (33.4 ± 6.5 mL/m2 vs. 26.3 ± 7.0 mL/m2, p < 0.001). There were no differences in global longitudinal strain (GLS) for either group overall (-19.3 ± 3.0% vs. -19.8 ± 1.6%, p = 0.52), but 17% of the jockey group demonstrated an abnormal GLS. Conclusions Jockeys have adaptations to their cardiac structure and function compared to the general population. Differences could be attributed to chronic physiological demands of racing and should be considered in future research involving jockeys.